IbM PADA KELOMPOK USAHA KECIL BERBASIS UPPKS DAN KUBE HIMPUNAN WIRAUSAHA TRANSMIGRASI - Asriati, Nuraini; Hidayat, -; Ulfah, Maria (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
This IBM program aimed: (1) accompany and guide a group of microbusiness productive economic country society in developing production partner I and partner II; (2) create a partnership sinergy that condusive between society and university. General cases that occur in partner are: (a) fund limitation, market ing, and media production that produce a lot of products, (b) don't have dry oven at rainy season, (c) lack of skill in doing diversification product, (d) don't do good accounting report management, (e) don't have label and hausehold food industry. The solutions are: (1) counseling and guidancein applying a loan in a bank; (2) socialization about diversification product by appropriate technology; (3) counseling and guidance in making accounting report; (4) counseling production and marketing management; (5) counseling and guidance in making labrl, i-household food industry, and kosher certificate. The implementation program of IBM done in 3 stages: (1) preparation stage, (2) implementation stage, (3) evaluation stage. The out put activities are a simple innovation technology of slicer crackers, earn fund by light subsidy from Mandiri Bank, Branch of Rasau Jaya, Household Food Industry Certificate, and kosher